MGIMO University Scientific Schools, 70th Anniversary - A. V. Torkunov (Vestnik MGIMO-Universiteta, 2014)
The article discusses the research and development achievements of MGIMO-University and lays out a framework for further development. The author the responses of the humankind to the challenges of history are bound with acute contradictions and chaos in social and international relations. Among the main tools for soothing the contradictions are education and science. The author dwells upon the issue of educating students for Foreign Service. The education programs should include a following subject triad: history of international relations, international law and macroeconomics. This suggestion reflects the developments in worlds top universities. Among the key competencies required for work at Foreign Crevice are inter cultural communication, political psychology and negotiation skills. Th earticle out lines a program for getting MGIMO University to the top of world league tables. This goal is fairly new for Russian higher education; nevertheless it finds great support and encouragement on the part of Russian government in the form of laws and development programs. The government sets a goal of making 5 to 10 Russian universities world's best. The 70 years history of excellent research, education and training is a good ground for MGIMO to achieve this goal.